Survey of Mental-Emotional Status of Junior High School Students in Bandung District, West Java Province, Indonesia - Gojali, A R (KnE Life Sciences, 2019)
Mental health is important factor for health adolescent future. Mental and emotional problems of the teenager is a specific health problem, and recently not threaten adequate especially in Bandung District. The main causes of mental-emotional problems in a teenager are school environment. Screening of mental-emotional problems is very important to prevents further noticeable behavior problem.The aim of the study was to describe mental-emotional problems in Junior High School students in Bandung District. This study uses a survey with the SDQ-strengths and difficulties questionnaire, interview and Focus Group Discussion. The sample of this population is the 8th-grade students in junior high school as much as 4650 students from 10 junior high schools. The results showed that student with normal mental - emotional status as much as 85.1% and borderlines mental - emotional status as much as 11.8% and abnormal mental emotional status as much as 1.9%. The student with the emotional disorder includes anxiety and depression; hyperactivity problems such as Attention Deficit Hyperactivity Disorder (ADHD) and peer problems such as bullying. Mentalemotional problems of the student should be adequate intervention. Suggested the need to conduct education, curricula modification, promote school healthcare, childparent communication, psychotherapy, and training to improve life skill competencies. Keywords: Teenager; student;mental-emotional problem; the SDQ